Experience and problems of usage of IT-Technologies in the system of air cargo services - U. G. Edigareva; A. V. Vlasov (Путеводитель предпринимателя)
The article deals with the problems ofdevelopment and use ofIT-Technologies in air cargo transportation,as well as a number of aspects of the interaction of air cargo carriers and customs services in the conditions of Russia’s membership in the EAEU.